The Creativity Premium - David Gill; Victoria L. Prowse (Institute of Labor Economics (IZA), 2021)
Success in life increasingly depends on key skills that allow people to thrive in education, the labor market, and their interactions with others. In this paper, we emphasize creativity as a key skill that is essential to open-ended problem solving and resistant to automation. We use rich longitudinal data to study the relationship between people's creativity measured in childhood and their individual attributes and life outcomes. We find that childhood creativity predicts labor market and educational success: more creative individuals earn more during the course of their careers, work in higher occupational categories, and reach higher levels of educational attainment. Our analysis of attributes further suggests that creative individuals have a package of practical skills that allows them to thrive in work environments where learning from experience is important. We combine insights from our findings with evidence from psychology to propose creativity-improving interventions that could lead to substantial economic benefits.
Keywords: D91; J24; 330; creativity; skills; life outcomes; children; longitudinal; labor market; wages; earnings; occupational category; educational attainment; practical skills; experience; cognitive ability; human capital